Hubungan antara Insomnia dengan Kualitas Hidup Mahasiswa Fakultas Kedokteran Universitas Katolik Indonesia Atma Jaya Jakarta - Patricia Adelia Daton; Herlina Uinarni; Satya Joewana (Universitas Hang Tuah, 2019)
ABSTRACT Association between Insomnia and Quality of Life among Students of Faculty of Medicine Atma Jaya Catholic University of Indonesia By: PATRICIA ADELIA DATON Supervised by: dr. Herlina Uinarni, Sp.Rad (K) Background: Insomnia is a worldwide health problem with high prevalence. Insomnia is defined as difficulties to sleep relating to onset, ability to maintain sleep, duration, and quality of sleep. Insomnia could lead to daytime activity dysfunction, which could further affect quality of life in a negative way. This research was conducted to analyze whether there is a correlation between insomnia and quality of life among students of Faculty of Medicine Atma Jaya Catholic University of Indonesia. Methods: This cross-sectional research was conducted on 107 students of Faculty of Medicine Atma Jaya Catholic University of Indonesia which suffice the inclusion criteria. Data were collected using research instruments Insomnia Severity Index (ISI) to evaluate insomnia grades, and World Health Organization Quality of Life - BREF(WHOQOL-BREF) to evaluate quality of life. Result: From a total of 107 respondents, 65 of the respondents have insomnia. Poor quality of life found in insomniac respondents are as follows: (49,2%) on the domain of physical, (63,1%) on the domain of psychological, (63,1%) on the domain of social relationships, and (43,1%) on the domain of environment. The p values found are 0,000 on the domain of physical, 0,000 on the domain of psychological, 0,022 on the domain of social relationships, and 0,010 on the domain of environment. Conclusion: There were a significant association between insomnia and quality of life among students of Faculty of Medicine Atma Jaya Catholic University of Indonesia. Keywords:Insomnia, Quality of Life, Medical Students.